Estimates of quaternary Philippine coastlines, land bridges, submerged river systems and migration routes A GRASS GIS approach - Robles, Emil Charles (Hukay, 2013)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/3964/3609